2018
DOI: 10.1111/pbi.12942
|View full text |Cite
|
Sign up to set email alerts
|

Finding invisible quantitative trait loci with missing data

Abstract: SummaryEvolutionary processes during plant polyploidization and speciation have led to extensive presence–absence variation (PAV) in crop genomes, and there is increasing evidence that PAV associates with important traits. Today, high‐resolution genetic analysis in major crops frequently implements simple, cost‐effective, high‐throughput genotyping from single nucleotide polymorphism (SNP) hybridization arrays; however, these are normally not designed to distinguish PAV from failed SNP calls caused by hybridiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
59
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 80 publications
(114 reference statements)
1
59
1
Order By: Relevance
“…Analysis of raw genotype data from the Brassica 60k SNP array 25,26 for a doubled haploid population ExR53-DH was performed for 244 genotypes. Two genetic maps were produced, one using only SNP markers (the "SNP map") and one using SNP plus SNaP markers 24 (the "SNaP map"), respectively. Comparison of the SNP and SNaP maps revealed that large chromosomal regions were not covered in the SNP map (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of raw genotype data from the Brassica 60k SNP array 25,26 for a doubled haploid population ExR53-DH was performed for 244 genotypes. Two genetic maps were produced, one using only SNP markers (the "SNP map") and one using SNP plus SNaP markers 24 (the "SNaP map"), respectively. Comparison of the SNP and SNaP maps revealed that large chromosomal regions were not covered in the SNP map (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…This study focuses exclusively on gene PAV in oilseed rape breeding populations and evaluates the biological relevance and prevalence of gene PAV associated with resistance to a common fungal disease of oilseed rape, Verticillium stem striping caused by Verticillium longisporum. By genetic mapping of genome-wide SNP/ SNaP markers 24 , along with short-read Illumina sequencing in combination with long-range optical mapping, we demonstrate that inclusion of presence-absence polymorphisms in quantitative trait locus (QTL) mapping strategies enables also reliable identification of gene PAV with a putative role in V. longisporum resistance. The results provide a valuable example for the importance of pangenomic gene variation for breeding of a key trait in a major polyploid crop.…”
mentioning
confidence: 99%
“…Examples demonstrating the contribution of such SV towards 37 eco-geographical adaptation and disease resistance in oilseed rape suggest that revisiting 38 complex plant genomes using medium-coverage, long-read sequencing might reveal 39 unexpected levels of functional gene variation, with major implications for trait regulation 40 and crop improvement. 41 visualization based on mRNAseq data (He et al, 2017) or deletion calling from SNP array 55 data (Gabur et al, 2018;Grandke et al, 2016). Critically, numerous examples have 56 connected genome SV in B. napus to important agronomic traits (Gabur et al, 2018; Gabur et 57 al., 2019;Liu et al, 2012;Stein et al, 2017).…”
mentioning
confidence: 99%
“…41 visualization based on mRNAseq data (He et al, 2017) or deletion calling from SNP array 55 data (Gabur et al, 2018;Grandke et al, 2016). Critically, numerous examples have 56 connected genome SV in B. napus to important agronomic traits (Gabur et al, 2018; Gabur et 57 al., 2019;Liu et al, 2012;Stein et al, 2017). These studies revealed the important role of SV 58 in the creation of de novo variation for adaptation and breeding, however the methods used 59were not yet capable of resolving SV at gene scale.…”
mentioning
confidence: 99%
“…Enhancing the opportunities to mine genome sequence data for previously invisible diversity (Gabur et al, 2018a) prolific Gabur et al, 2018b). For example, there is growing evidence that novel genome structural variants in B. napus are created even during self-pollination of homozygous cultivars or during generation of doubled haploid lines (He et al, 2017).…”
mentioning
confidence: 99%